2004
DOI: 10.1207/s15328007sem1104_3
|View full text |Cite
|
Sign up to set email alerts
|

Bias in the Correlated Uniqueness Model for MTMM Data

Abstract: This simulation investigates bias in trait factor loadings and intercorrelations when analyzing multitrait-multimethod (MTMM) data using the correlated uniqueness (CU) confirmatory factor analysis (CFA) model. A theoretical weakness of the CU model is the assumption of uncorrelated methods. However, previous simulation studies have shown little bias in trait estimates even when true method correlations are large. We hypothesized that there would be substantial bias when both method factor correlations and meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
62
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(69 citation statements)
references
References 42 publications
(59 reference statements)
7
62
0
Order By: Relevance
“…In addition, the correlated uniqueness model is known to have bias when there are strong loadings on methods factors and strong correlations between method factors, which is a characteristic of our data (see Figure 2 below for loadings on method factors; Conway et al, 2004). Because the emotion factors are indicated by only two manifest variables, we added an additional constraint to adequately identify the emotion latent variable by constraining the unstandardized loadings from both manifest variables to equality forcing the affective and cognitive emotion subscale to load equally on the corresponding emotion latent factor 3 .…”
Section: Resultsmentioning
confidence: 92%
“…In addition, the correlated uniqueness model is known to have bias when there are strong loadings on methods factors and strong correlations between method factors, which is a characteristic of our data (see Figure 2 below for loadings on method factors; Conway et al, 2004). Because the emotion factors are indicated by only two manifest variables, we added an additional constraint to adequately identify the emotion latent variable by constraining the unstandardized loadings from both manifest variables to equality forcing the affective and cognitive emotion subscale to load equally on the corresponding emotion latent factor 3 .…”
Section: Resultsmentioning
confidence: 92%
“…Similarly, the use of multisource performance ratings (e.g., by supervisors, peers, and subordinates, a.k.a., 360-degree assessment) is considered an optimal method for evaluating job performance (Conway & Huffcutt, 1997; Lance et al, 2008). Because each informant observes the target within a specific relationship and context, it is desirable to obtain ratings from multiple informants privy to different settings to obtain a comprehensive assessment, particularly when behavior may vary over contexts.…”
mentioning
confidence: 99%
“…Instead, it is assumed that the effects of different raters are independent of each other. This is not always a plausible assumption and Conway, Lievens, Scullen, and Lance (2004) showed that biased estimates for the trait variances and covariances may result if the assumption of uncorrelated method effects is not met. Furthermore, because the method effects are only accounted for by allowing for covariances between error variables, no explanatory variables can be included in the model that may explain the interindividual differences in the method effects.…”
Section: The Correlated Trait-correlated Uniqueness Modelmentioning
confidence: 99%